1988
DOI: 10.1128/mcb.8.10.4295
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of pp60v-src: myristylation in a cell-free system.

Abstract: Covalent attachment of myristic acid to pp6o0-sc, the transforming protein of Rous sarcoma virus, was studied in a cell-free system. Using a synthetic peptide containing the first 11 amino acids of the mature pp60 V-src polypeptide sequence as a substrate, we probed lysates from a variety of cells and tissues for N-myristyl transferase (NMT) activity. Nearly every eucaryotic cell type tested contained NMT, including avian, mammalian, insect, and plant cells. Since NMT activity was detected in rabbit reticulocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(127 citation statements)
references
References 45 publications
4
123
0
Order By: Relevance
“…The detection of a broader reactive band corresponding to Calymmin, in both in vitro transcription-translation and embryo protein extracts, may suggest the existence of posttranslational modifications of the peptide both in vivo and in cell-free systems. This would agree with the various N-and mucin type Oglycosylation conserved motifs, and the high number of potential N-myristoylation sites found in the amino acid sequence of Calymmin (e.g., Deichaite et al, 1988).…”
Section: Protein Characterization and Cellular Localization Of Calymmsupporting
confidence: 77%
“…The detection of a broader reactive band corresponding to Calymmin, in both in vitro transcription-translation and embryo protein extracts, may suggest the existence of posttranslational modifications of the peptide both in vivo and in cell-free systems. This would agree with the various N-and mucin type Oglycosylation conserved motifs, and the high number of potential N-myristoylation sites found in the amino acid sequence of Calymmin (e.g., Deichaite et al, 1988).…”
Section: Protein Characterization and Cellular Localization Of Calymmsupporting
confidence: 77%
“…Since both NMTs and methionine aminopeptidases function cotranslationally while the nascent polypeptide chain is still attached to the ribosomes (20,36,37), it might be possible to speculate that these two enzymes may share similar restrictions with respect to their substrate specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Since the in vitro translation system using rabbit reticulocyte lysate contains the components involved in cotranslational protein N-myristoylation and N-acetylation (17,19,20), the use of this system to study cotranslational protein modification seems to be appropriate. In fact, we previously demonstrated that tumor necrosis factor (TNF), a nonmyristoylated model protein, could be efficiently myristoylated in the in vitro trans-lation system when an N-myristoylation motif of Rasheed leukemia virus-Gag protein or G i1 ␣ protein was linked to the mature domain of TNF (21,22).…”
Section: From the Department Of Biological Chemistry And §Department mentioning
confidence: 99%
“…Because the mechanism for N-terminal myristoylation appears to be conserved in Drosophila (Deichaite et al, 1988;Ntwasa et al, 1997;Benting et al, 2000), it is likely that Nullo exists as a myristoylprotein in vivo.…”
Section: Nullo Is Modified By N-terminal Myristoylationmentioning
confidence: 99%
“…First, the consensus target for NMT activity appears to be well conserved between Drosophila and other organisms. Both Drosophila embryonic extracts and Schnieder cells have been shown to have an NMT activity that modifies myristoyl proteins from other organisms in a specific manner, and the corresponding NMT gene has been shown to be expressed before cellularization (Deichaite et al, 1988;Ntwasa et al, 1997;Benting et al, 2000). Second, the glycine to alanine mutation which blocks myristoylation in vitro has a striking effect on the subcellular localization of Nullo in vivo, suggesting that the N-myristoylation site is important for the targeting of Nullo to the plasma membrane.…”
Section: N-terminal Motifs Control the Localization Of Nullo Proteinmentioning
confidence: 99%